J. Norman Collie, the inventive chemist. (1st March 2014) - Davies, Alwyn
Norman Collie was Professor of Organic Chemistry and Director of Laboratories at University College London between 1902 and 1928. He was a pioneering mountaineer but was also a prolific inventor; this review focuses on that little-known latter aspect of his activities.